2022
DOI: 10.37934/araset.29.1.129141
|View full text |Cite
|
Sign up to set email alerts
|

Covid 19: Implementation of Digital Interactive Teaching and Learning (Ditl) in the ‘Statistics for Social Science’ Course

Abstract: The spread of COVID-19 has drastically changed the community's norms or lifestyles, including public or private servants working from home (WFH). WFH also occurs among staff at the school and university. All students and educators were encouraged to continue their teaching and learning sessions online. The lecturers had to continue teaching and learning (T&L) at the university level via e-learning or electronic learning, including calculation courses such as statistics. At UUM, the ‘Statistics for Social S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…For instance, research conducted by Austerschmidt et al [48] investigated the effectiveness of video presentations on variance and covariance, revealing that the use of videos significantly improved students' skills compared to those who solely relied on reading text material. Furthermore, Chik et al [50] addressed the impact of virtual teaching and learning during the pandemic, demonstrating that online teaching methodologies, such as interactive learning through technology, can prove effective even in crisis situations. Collectively, these studies underscore the effectiveness of approaches such as blended learning, video integration, and adaptation to virtual environments, providing a robust evidence base to enhance the discussion on teaching methods in virtual statistics education.…”
Section: B Student-focused Teaching Methodsmentioning
confidence: 99%
“…For instance, research conducted by Austerschmidt et al [48] investigated the effectiveness of video presentations on variance and covariance, revealing that the use of videos significantly improved students' skills compared to those who solely relied on reading text material. Furthermore, Chik et al [50] addressed the impact of virtual teaching and learning during the pandemic, demonstrating that online teaching methodologies, such as interactive learning through technology, can prove effective even in crisis situations. Collectively, these studies underscore the effectiveness of approaches such as blended learning, video integration, and adaptation to virtual environments, providing a robust evidence base to enhance the discussion on teaching methods in virtual statistics education.…”
Section: B Student-focused Teaching Methodsmentioning
confidence: 99%
“…It has been observed that the blended learning technology resulted in enhanced extent of learning (in the form of academic achievements, ideas, and knowledge), permanence (in the form of retention of learning), student engagement (in the form of mutual interaction between students and teachers as well as between students) and student satisfaction (towards learning activities) [19,20]. To sum up, blended learning technology may simply be considered the best possible integration of conventional classroom face-to-face learning experiences with any non-conventional online learning experiences.…”
Section: Blended Learning Technologiesmentioning
confidence: 99%
“…In addition, the closure of educational institutions necessitated the rapid transition to online education and e-learning platforms mentioned in [5][6][7][8]. As traditional classroom settings became inaccessible, educational systems faced the challenge of ensuring uninterrupted learning experiences for students [9,10].…”
Section: Introductionmentioning
confidence: 99%